Nanoscale Friction: Phonon Contributions for Single and Multiple Contacts - Streator, Jeffrey L. (Frontiers in Mechanical Engineering, 2019)
A generic model has been developed to simulate the effect of phonon interactions during nanoscale sliding with an incommensurate interface. A rigid slider or array of sliders is translated across a 3D elastic slab whose mass elements are harmonically coupled, either in a simple cubic structure (for vast majority of cases) or in a face-centered cubic structure Each slider interacts with the slab via the Lennard-Jones 6-12 intermolecular potential. Elastic waves are allowed to propagate without any damping and no energy is removed from the system. Boundary conditions are set sufficiently remotely that no significant wave energy returns to the interface from boundary reflection. Simulation results demonstrate that for such nanoscale contacts, (1) the presence of one slider can affect the friction felt by another slider through phonon generation; (2) friction force scales with contact width rather than with contact area and (3) the friction force may be sensitive to the number of contact regions that comprise a given total area.